Measuring reliable change in cognition using the Edinburgh Cognitive and Behavioural ALS Screen (ECAS) - Pender, Niall; Hardiman, Orla (My University, 2018)
Background: Cognitive impairment affects approximately 50% of people with amyotrophic lateral sclerosis (ALS). Research has indicated that impairment may worsen with disease progression. The Edinburgh Cognitive and Behavioural ALS Screen (ECAS) was designed to measure neuropsychological functioning in ALS, with its alternate forms (ECAS-A, B, and C) allowing for serial assessment over time. Objective: The aim of the present study was to establish reliable change scores for the alternate forms of the ECAS, and to explore practice effects and test-retest reliability of the ECAS’s alternate forms. Method: Eighty healthy participants were recruited, with 57 completing two and 51 completing three assessments. Participants were administered alternate versions of the ECAS serially (A-B-C) at four-month intervals. Intra-class correlation analysis was employed to explore test-retest reliability, while analysis of variance was used to examine the presence of practice effects. Reliable change indices (RCI) and regression-based methods were utilized to establish change scores for the ECAS alternate forms. Results: Test-retest reliability was excellent for ALS Specific, ALS Non-Specific, and ECAS Total scores of the combined ECAS A, B, and C (all > .90). No significant practice effects were observed over the three testing sessions. RCI and regression-based methods produced similar change scores. Conclusion: The alternate forms of the ECAS possess excellent test-retest reliability in a healthy control sample, with no significant practice effects. The use of conservative RCI scores is recommended. Therefore, a change of ≥8, ≥4, and ≥9 for ALS Specific, ALS Non-Specific, and ECAS Total score is required for reliable change
PUBLISHED
Keywords: Cognition; Edinburgh Cognitive andBehavioural ALS Screen (ECAS); Alternate forms; Test reliability; Practice